Odpowiedzi

2010-03-04T15:56:14+01:00
A)
(2x+4y)-(5+2x)-(3y-5) =
2x+4y-5-2x-3y+5 =
2*1+4*2-5-2*1-3*2+5 =
2+8-5-3-6+5 =
2

b)
4a(kwadrat)-(3a(kwadrat)-4a+1)-(-2a(kwadrat)+a) =
4a²-3a²+4a-1+2a²-a =
4*(-3)²-3*(-3)²+4*(-3)-1+2*(-3)²-(-3) =
36-27-12-1+18+3 =
17
2010-03-04T15:57:37+01:00
(2x+4y)-(5+2x)-(3y-5) dla x=1 i y=2
(2x1+4x2)-(5+2x1)-(3x2-5)
(2+8)-(5+2)-(6-5)
10-7-1
3-1
2

4a(kwadrat)-(3a(kwadrat)-4a+1)-(-2a(kwadrat)+a) dla a=-3
4x(-3)kwadrat-(3x(-3)kwadrat-4x(-3)+1)-(-2(-3)kwadrat+(-3))
4x9-(3x9+12+1) -(-2x9+(-3))
36-(27+12+1) - (-18+(-3))
36 - 40 - (-21)
-4 - (-21)
-25